Currency hedging with help of derivatives - Sylvie Riederová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2011)
The high volatility combined with unpredictable fluctuations of CZK had shown one more time to the Czech exporting companies the necessity of currency hedging. This article is focused on finding of suitable currency hedging instrument for exporting company, working with the currency pair of CZK/EUR. In the first part, the time series analysis is made for volatility, interest rates and exchange rate. Based on the real market data – gained from Thomson REUTERS and CNB for the time period starting in 2002 – the detailed analysis is made in graphical form. The main goal is to find out the future trends with help of liner regression analysis, based on the historical data. Several graphs are provided with the trend line end estimated interval (min and max) for the each variable. The calculated values are clearly marked, to be separated from the real market data. Exchange rate curve shows the market behaviour in the last years and is to be used as most important indicator for the future trends. Interest rates curves are very important for the calculation of the BIPS (basis points), determining the price of the forwards. The difference between landing and deposit rates for the same period of time and different currencies are showing the market estimation of the future development of each currency. Forward price is to be seen as a benchmark for the all other financial instruments. And finally the volatility (quoted as middle) is very important part in the pricing of currency options.The second part is closely connected with the first one. Based on the results of provided analyses, it recommends a suitable hedging product for the next period of time. All of the analyses are taken as an input in different ways. The volatility is important for the decision of selling or purchasing the specific part of currency option. The exchange rate outlook together with the interest rates is the indicator of the future development of the currency pair and is playing the most important role in the decision process regarding the kind of hedging.